Lymphocytic Infiltration of Epithelium in Diagnosis of Gluten-sensitive Enteropathy. Issue 5823 (12th August 1972) - Fry, Lionel; Seah, P. P.; McMinn, R. M. H.; Hoffbrand, A. V.
Abstract : The macroscopic appearance of the mucosa of the small intestine and the lymphocytic infiltration of the epithelium were studied in 27 patients with dermatitis herpetiformis and in 11 control subjects. The mucosa was abnormal in appearance in 13 of the patients and normal in 14 patients and in all the controls. In 25 (93%) of the patients the intraepithelial lymphocyte count was significantly raised compared with the controls. The increased lymphocytic infiltration of the epithelium in the patients probably represented an underlying immunological reaction of the small intestine to gluten, since the infiltration lessened in five out of six patients after a year on a gluten-free diet and in all of four patients after three years on a gluten-free diet. Increased lymphocytic infiltration of the epithelium of the small intestine seems a surer sign of gluten sensitivity than the macroscopic appearance of the mucosa, and a diagnosis of gluten-sensitive enteropathy may no longer be excluded when the mucosa appears normal. Further evidence of the significance of increased lymphocytic infiltration is that patients with normal-looking mucosa but with raised intraepithelial lymphocyte counts often had low serum folate levels.